2022
DOI: 10.1038/s41586-022-04962-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde movements determine effective stem cell numbers in the intestine

Abstract: Morphology and functionality of the epithelial lining differ along the intestinal tract, yet tissue renewal at all sites is driven by stem cells at the base of crypts 1-3 . Whether stem cell numbers and behaviour vary at different sites is unknown. Here, we show by intravital microscopy that despite similarities in the number and distribution of proliferative cells with an Lgr5 signature, small intestinal (SI) crypts contain twice as many effective stem cells as large intestinal (LI) crypts. We find that, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…We evaluated autophagic state as a predictor of f‐ISC potential and found that cells with high autophagic vesicle content exhibit plasticity in vitro , are protected from injury in vivo , and are biased toward noncycling secretory lineages and against cycling stem and absorptive progenitor cells. A recent study demonstrated that organoid‐formation efficiency is inversely correlated with Lgr5‐GFP expression in the small intestine, lending support to our findings that cellular plasticity in vitro is enhanced within differentiated secretory cells compared with CBCs and Lgr5‐expressing progenitors (Azkanaz et al , 2022). The requirement for autophagy in intestinal regeneration has been demonstrated previously using pan‐epithelial genetic ablation (Asano et al , 2017; Trentesaux et al , 2020), although these studies did not dissect the contribution of autophagy prior to injury versus a requirement for injury‐induced autophagy.…”
Section: Discussionsupporting
confidence: 88%
“…We evaluated autophagic state as a predictor of f‐ISC potential and found that cells with high autophagic vesicle content exhibit plasticity in vitro , are protected from injury in vivo , and are biased toward noncycling secretory lineages and against cycling stem and absorptive progenitor cells. A recent study demonstrated that organoid‐formation efficiency is inversely correlated with Lgr5‐GFP expression in the small intestine, lending support to our findings that cellular plasticity in vitro is enhanced within differentiated secretory cells compared with CBCs and Lgr5‐expressing progenitors (Azkanaz et al , 2022). The requirement for autophagy in intestinal regeneration has been demonstrated previously using pan‐epithelial genetic ablation (Asano et al , 2017; Trentesaux et al , 2020), although these studies did not dissect the contribution of autophagy prior to injury versus a requirement for injury‐induced autophagy.…”
Section: Discussionsupporting
confidence: 88%
“…These LGR5+ cells in the center of the crypt can initiate the differentiation process under the suitable conditions. 2 These results indicate that structural characteristics of all crypts in the whole intestines are consistent with functional roles of LGR5+ cells, implying a stable dynamic repair mechanism in healthy intestines. 2 This is essential for maintenance of the intestinal environment and epithelial functions.…”
supporting
confidence: 70%
“…They found that in large intestine (LI) crypts, marginal Lgr5 -positive (LGR5+) cells lack retrograde movement and are unable to effectively function for long periods of time. 2 These results suggest that LGR5+ cells can effectively self-renew and further differentiate in the intestines only in a specific environment containing niche cells.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Specifically, from all dedifferentiated cells, about 60% were Paneth cells, 30% absorptive progenitors and 10% secretory progenitors, which could be considered quiescent +4 stem cells as previously suggested (53). Furthermore, we used our model to explore the retrograde motion, reported using intravital microscopy (54), of cells returning to the niche to de-differentiate into stem cells. For cells outside the niche, movement is retrograde when its velocity is negative in the z direction.…”
Section: Resultsmentioning
confidence: 99%